Effect of Economic Policies on Income Inequality: A Comparative Study of Switzerland and Bolivia - Weber, Adrian (International Journal of Economics, 2024)
Purpose: The aim of the study was to examine the effect of economic policies on income inequality: a comparative study of Switzerland and Bolivia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Switzerland, with its advanced economy, implements progressive tax policies, robust social welfare programs, and equitable education systems, contributing to relatively low income inequality. In contrast, Bolivia, a developing nation, faces challenges in reducing income inequality due to less effective economic policies, limited social safety nets, and a larger informal sector. The study underscores that while Switzerland's policies effectively mitigate income disparities, Bolivia's efforts are hindered by structural economic issues and policy limitations. Unique Contribution to Theory, Practice and Policy: The Kuznets curve theory, the human capital theory & the social stratification theory may be used to anchor future studies of climate change on risk management practices in agriculture in Switzerland. From a practical perspective, the study provides actionable insights for improving the design and implementation of economic policies. The study offers several policy recommendations for both developed and developing economies. Policymakers in Switzerland should consider revising tax policies to address the increased burden on higher-income individuals and improve the overall equity of the system.